APPLICATIONS IN FOREIGN CURRENCY MONEY CHANGER CV.XYZ USING MICROSOFT VISUAL BASIC 6.0 - Fanny Ramadhan; Hariyanto.,SKom., MMSI Hariyanto.,SKom., MMSI (Jurnal Sistem Informasi, 2010)
This explains the scientific writing about the design of application programs forforeign currency transactions by using Visual Basic 6.0 programming languagecoupled with the flow diagram (flowchart).In scientific writing database is used also by using Microsoft software Accsess 2003which have been integrated in Visual Basic 6.0 program itself. Consists of four tablesof Currency, Customer, Transaction, Employee.In the end application program for foreign currency transactions will be applied tocompanies or services that are engaged in foreign exchange notabennya still usemanual way, or not to optimize existing computer systems to facilitate the conduct oftransactions, such as creating a memorandum of the transaction and making a report.